Designing training in organic farming on a multinational basis. Issue 2 (7th March 2016) - Guiné, Raquel P.F.; Costa, Daniela V.T.A; Correia, Paula M.R.; Costa, Cristina A.; Correia, Helena E.; Castro, Moises; Guerra, Luis T; Seeds, Catherine; Coll, Collette; Radics, Laszlo; Arslan, Meahmet; Soylu, Soner; et al.
Abstract : Purpose: – The purpose of this paper is to obtain information to characterize potential trainees seeking training programs about organic farming in the form of mobile learning. This information is expected to allow for establishing a set of guidelines to design mobile training opportunities that could match the potential clients' wishes. Design/methodology/approach: – For this survey an on-line questionnaire was used, translated into the languages of the participating countries (Portugal, Spain, Slovakia, Hungary, UK, Italy and Turkey), and in the end 133 consented valid questionnaires were obtained. The data analysis was made with SPSS and included basic descriptive statistics, crosstabs and χ 2 tests, considering a level of significance of 5 per cent. Findings: – The results obtained in the present study indicate that designing training programs in organic farming for a wide target population should attend to the differences between countries, which showed to significantly influence the preferences of the possible clients for this type of training. Practical implications: – This study provided valuable information for use in the preparation of training programs for adults who want to expand their knowledge on organic farming, in order to prepare courses more in accordance with their preferences. Originality/value: – The fact that the study was undertaken in several countries, including North, Central and South Europe, is a positive indicator that globally accepted courses could be implemented successfully. To the knowledge no such work was undertaken up to the present, thus confirming the originality of the study presented.